Activation/Deactivation Free-Energy Profiles for the β2-Adrenergic Receptor: Ligand Modes of Action - Calderon Reyes, Jacqueline; Ibrahim, Passainte; Gobbo, Dorothea; Gervasio, Francesco Luigi; Clark, Timothy (Journal of Chemical Information and Modeling, 2023)
We use enhanced-sampling simulations with an effective collective variable to study the activation of the β2-adrenergic receptor in the presence of ligands with different efficacy. The free-energy profiles are computed for the ligand-free (apo) receptor and binary (apo-receptor + G-protein α-subunit and receptor + ligand) and ternary complexes. The results are not only compatible with available experiments but also allow unprecedented structural insight into the nature of GPCR conformations along the activation pathway and their role in the activation mechanism. In particular, the simulations reveal an unexpected mode of action of partial agonists such as salmeterol and salbutamol that arises already in the binary complex without the G-protein. Specific differences in the polar interactions with residues in TM5, which are required to stabilize an optimal TM6 conformation that facilitates G-protein binding and receptor activation, play a major role in differentiating them from full agonists.
CRIS-Team Scopus Importer:2023-11-10

Determinants of Neutral Antagonism and Inverse Agonism in the β2-Adrenergic Receptor - Calderon Reyes, Jacqueline; Ibrahim, Passainte; Gobbo, Dorothea; Gervasio, Francesco Luigi; Clark, Timothy (Journal of Chemical Information and Modeling, 2024)
Free-energy profiles for the activation/deactivation of the β2-adrenergic receptor (ADRB2) with neutral antagonist and inverse agonist ligands have been determined with well-tempered multiple-walker (MW) metadynamics simulations. The inverse agonists carazolol and ICI118551 clearly favor single inactive conformational minima in both the binary and ternary ligand-receptor-G-protein complexes, in accord with the inverse-agonist activity of the ligands. The behavior of neutral antagonists is more complex, as they seem also to affect the recruitment of the G-protein. The results are analyzed in terms of the conformational states of the well-known microswitches that have been proposed as indicators of receptor activity.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Agonists; Antagonists; Conformation; Ligands; Receptors

General Metadynamics Protocol To Simulate Activation/Deactivation of Class A GPCRs: Proof of Principle for the Serotonin Receptor - Calderon Reyes, Jacqueline; Ibrahim, Passainte; Gobbo, Dorothea; Gervasio, Francesco Luigi; Clark, Timothy (Journal of Chemical Information and Modeling, 2023)
We present a generally applicable metadynamics protocol for characterizing the activation free-energy profiles of class A G-protein coupled receptors and a proof-of-principle study for the 5HT1A-receptor. The almost universal A100 activation index, which depends on five inter-helix distances, is used as the single collective variable in well-tempered multiple-walker metadynamics simulations. Here, we show free-energy profiles for the serotonin receptor as binary (apo-receptor + G-protein-α-subunit and receptor + ligand) and ternary complexes with two prototypical orthosteric ligands: the full agonist serotonin and the partial agonist aripiprazole. Our results are not only compatible with previously reported experimental and computational data, but they also allow differences between active and inactive conformations to be determined in unprecedented atomic detail, and with respect to the so-called microswitches that have been suggested as determinants of activation, giving insight into their role in the activation mechanism.
CRIS-Team Scopus Importer:2023-06-02